Membrane-associated RNA-binding proteins orchestrate organelle-coupled translation - Béthune, Julien (Trends in cell biology, 2019)
Proteins are positioned and act at defined subcellular locations. This is particularly important in eukaryotic cells that deliver proteins to membrane-bound organelles such as the endoplasmic reticulum (ER), mitochondria, or endosomes. It is axiomatic that organelle targeting depends mainly on polypeptide signals. However, recent results demonstrate that targeting elements within the encoding transcripts are essential for efficient protein localisation. Key readers of these elements are membrane-associated RNA-binding proteins (memRBPs) that orchestrate organelle-coupled translation. The translation products then either cross the membrane for organelle entry or hitchhike on organelle surfaces for complex assembly and co-transport. Understanding the interaction of protein- and RNA-based targeting signals is essential to decipher the molecular basis for mutant phenotypes in disease.